(untitled) (Applied Biological Research, 2017)
Current study was designed to evaluate the antifertility effects of nifedipine, a pharmaceutical medicament for high blood pressure. Mature and healthy male lesser Bandicoot rats, Bandicota bengalensis Gray and Hardwicke, were fed on bait (cracked wheat, powdered sugar, groundnut oil 98:2:2) containing 0.1 and 0.05% nifedipine for 12 days in no-choice feeding test to record antifertility effects of nifedipine. The factors studied were the effect on weight of reproductive organs, sperm parameters in cauda epididymal fluid, breeding performance and histo morphology of testis. Nifedipine treatment significantly (P <0.05) reduced the weight of seminal vesicles and prostate gland in treated groups as ompared to untreated group. Sperm motility, live sperm count, sperm density and sperm morphology differed significantly between untreated and treated groups. The breeding performance of treated male rats was found reduced by 40-60% as compared to untreated ones. A significant effect of nifedipine treatment was observed on the number of germinal cells in seminiferous tubules. The study indicates the effect of nifedipine on fertility of male rats.